The Commissive Acts in Joe Biden’s Inauguration Speech - Pijar Omar Piscesco; Ambalegin, Ambalegin (Asosiasi Ide Bahasa Kepri, 2023)
The commissive acts in the inauguration speech by Joe Biden were identified in this descriptive qualitative research. The data used Cruse (2006) theory to analyze the types of commissive act. The data for this research was collected by using an observational method and a non-participation technique. Then, the data was analyzed using the pragmatic identity method and pragmatic competence in equalizing. The researchers identified in 15 utterances that uttered by Joe Biden in the presidential inauguration speech. The utterances consisted of 5 types of commissive acts. Those were 5 acts of promising, 1 act of offering, 3 acts of vowing, 2 acts of contracting, and 4 acts of pledging. Furthermore, from all those types, the acts of promising became the most dominant among the other types of commissive act from the 15 utterances that had been identified.